2016
DOI: 10.3946/kjme.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

Use of social media in education among medical students in Saudi Arabia

Abstract: PurposeSocial media (SM), a virtual place where people can share, exchange, and communicate their ideas and knowledge, has become the new trend in communication and learning. This study aims to explore Saudi Arabian medical students’ usage of SM and to discover the most common resources used in medical education. Furthermore, it aims to illustrate students’ belief about the influence of SM on their learning.MethodsThis cross-sectional study administered validated questionnaires to medical students from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 14 publications
4
46
3
6
Order By: Relevance
“…The study was conducted among medical universities in Saudi Arabia by Alsuraihi AK et al, in 2016, stated that 95.8% of the students felt that social media learning was beneficial, 40% of the students thought using social media might be distracting during the period of learning. While in the current study 86% found it beneficial [16].…”
Section: Recentcontrasting
confidence: 56%
“…The study was conducted among medical universities in Saudi Arabia by Alsuraihi AK et al, in 2016, stated that 95.8% of the students felt that social media learning was beneficial, 40% of the students thought using social media might be distracting during the period of learning. While in the current study 86% found it beneficial [16].…”
Section: Recentcontrasting
confidence: 56%
“…Alsuraihi, Almaqati, Abughanim, and Jastaniah (2016) [8] argue that social media is gradually becoming an important communication tool in the 21 st century penetrating academia at uncontrollable levels. This is because the social media platforms act as alternative information focal points thus students use in the compilation of their research projects.…”
Section: Medical Education In Saudi Arabiamentioning
confidence: 99%
“…For example, a tweet or post that is shared extensively on a social media platform may be inclined to be true and factual. It is important to acknowledge that not all truthful information is factual (Alsuraihi et al, 2016) [8].…”
Section: Medical Education In Saudi Arabiamentioning
confidence: 99%
See 1 more Smart Citation
“…Closed groups specialized in higher education are already frequent. The use of these new platforms to exchange, share and communicate ideas and knowledge among students, in particular Medicine, open new possibilities in student-teacher relations [6]- [17]. Students are very familiar with the use of social networks, access daily and from multiple devices.…”
Section: Introductionmentioning
confidence: 99%